Globalisation, Poverty and Inequality: A Computable General Equilibrium Microsimulation Analysis of the Impact of Trade Liberalisation in South Africa - (:unkn) unknown (My University, 2006)
The literature about the effects of globalisation on poverty and inequality in developing countries has been flourishing. However, there is no consensus emerging about the nature of this relationship since the observed effects of globalisation are typically country-specific. This suggests that the structure of the economy has to be taken into consideration when examining globalisation's impacts. The focus of this study is on South Africa, which is an interesting country given its history and its recent commitment to globalisation. Since the end of the apartheid era, trade liberalisation policies have been on top of the political agenda. In a country where poverty and inequality both stand at a very high level, it is particularly important to examine the microeconomic impact of trade policies. In this thesis, a computable general equilibrium model is combined with a microsimulation model in a sequential approach in order to build an effective tool to assess the effects of trade policies on South African households. This novel approach enables us to analyse in detail the microeconomic effects (on poverty and inequality) of a macroeconomic policy (trade liberalisation). The results suggest that the impact of trade liberalisation is pro-poor and mainly driven by the expansion of formal sector employment. However, the magnitude of the effects is fairly small.
Keywords: African Research